ANALYSIS OF THE EFFECT OF PROVIDING POSTER MEDIA, ANIMATED VIDEOS, AND TIKTOK VIDEOS ON PERSONAL HYGIENE SANITATION OF STREET VENDORS - Audia, Annisa Rahma; Kurniasari, Ratih (HEARTY, 2024)
Food processing that does not pay attention to personal hygiene, cleanliness around and food ingredients can cause contamination of disease sources. Hygiene sanitation of street food vendors is an effort to maintain food safety. This study aims to determine the personal hygiene sanitation of street food vendors. The research method uses a survey, conducted by asking several questions in the form of test questions and statements in the form of a questionnaire. Data analysis that will be used in this study is univariate analysis to determine the frequency distribution and bivariate analysis, to determine the relationship between the level of knowledge and attitudes of street vendors with food processing sanitation hygiene behavior. The results showed that the knowledge of street vendors along the road H.S Ronggo Waluyo Karawang city has increased, the attitude of traders has increased. Only poster education media is significant to knowledge and attitude p value = 0.00. The conclusion of this study proves that the direct attitude practice of personal hygiene sanitation in street vendors has not been implemented properly.